Socjolekt szlachecki w Pacholęciu hetmańskim Wincentego Pola (rekonesans) - Bryła, Władysława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The author discusses the manifestations of the ways in which noblemen talked about and evaluated social and family life. He brings attention to the cult of a family home, respect for home tradition, brotherhood of the nobility and the will to get to know the world.